Epidemiology of Community-Acquired Pneumonia in Edmonton, Alberta: An Emergency Department-Based Study - Thomas J Marrie; Jane Q Huang (Canadian Respiratory Journal)
Patients aged 17 years and older who presented to seven emergency departments in Edmonton, Alberta over a two-year period with community-acquired pneumonia (n=8144) were studied. The admission rates were 271/100,00 and 296/100,000 persons for year 1 and year 2 of the study, respectively. The admission rate increased with increasing age, peaking at 4639/100,000/year for those 90 years of age and older. In contrast, the percentage of patients who were admitted to an intensive care unit was highest for those in the younger age groups between 17 and 59 years of age. From 59 years of age and older, there was a progressive decline in the percentage of patients admitted to an intensive care unit, with approximately 1% of those in the 90 years and older age group admitted. A pronounced seasonal effect on the number of patients presenting to emergency department was also noted. During the winter months, there was up to a 50% increase in the number of cases compared with the summer months.